Impact of the COVID-19 pandemic on paediatric orthopaedic trauma workload in central London: a multi-centre longitudinal observational study over the "golden weeks": The COVid Emergency Related Trauma and orthopaedics (COVERT) Collaborative. (5th December 2020) - Sugand, Kapil; Park, Chang; Morgan, Catrin; Dyke, Rory; Aframian, Arash; Hulme, Alison; Evans, Stuart; Sarraf, Khaled M; Baker, Camilla; Bennett-Brown, Katharine; Simon, Henry; Bray, Edward; et al.
Abstract : Background and purpose — The COVID-19 pandemic has been recognised as an unprecedented global health crisis. This study assesses the impact on a large acute paediatric hospital service in London, evaluating the trends in the acute paediatric orthopaedic trauma referral caseload and operative casemix before (2019) and during (2020) COVID-19 lockdown. Patients and methods — A longitudinal retrospective observational prevalence study of both acute paediatric orthopaedic trauma referrals and operative caseload was performed for the first 6 "golden weeks" of lockdown. These data were compared with the same period in 2019. Statistical analyses included median (± median absolute deviation), risk and odds ratios as well as Fisher's exact test to calculate the statistical significance, set at p ≤ 0.05. Results — Acute paediatric trauma referrals in 2020 were reduced by two-thirds compared with 2019 (n = 302 vs. 97) with a halving risk (RR 0.55) and odds ratios (OR 0.43) of sporting-related mechanism of injuries (p = 0.002). There was a greater use of outpatient telemedicine in the COVID-19 period with more Virtual Fracture Clinic use (OR 97, RR 84, p < 0.001), and fewer patients being seen for consultation and followed up face to face (OR 0.55, RR 0.05, p < 0.001). Interpretation — The impact of the COVID-19 pandemic has led to a decline in the number of acute paediatric trauma referrals, admissions, and operations during the COVID period. There has also been a significant change in the patient pathway with more being reviewed via the means of telemedicine to reduce the risk of COVID-19 transmission and exposure. More work is required to observe for similar trends nationwide and globally as the pandemic has permanently affected the entire healthcare infrastructure.